Motivational interviewing in child sexual abuse investigations: Approaches shown to increase suspect engagement and information gathering during police interviews - Humann, Michael (International journal of police science & management, 2023)
On average, more than 200 child sex offences were recorded by UK police every day in 2020, and investigations for offences including rape, online grooming and sexual assault against children in the United Kingdom (UK) increased by 57% from 2014/15 to 2019/20. The interview process is central to information gathering, but empirical research regarding the obtention of information through child sexual abuse (CSA) suspect interviewing is still limited. The current study analyses 45 hours of interviews with CSA suspects focusing on behaviours consistent (and inconsistent) with motivational interviewing (MI) using the Observing Rapport-Based Interpersonal Techniques coding manual. In line with previous research demonstrating the efficacy of MI with terrorist suspects, this article focuses on the same four key interviewer skills identified in the therapeutic literature (reflective listening, summarising, rolling with resistance and developing discrepancies). It looks at their effects on information yield (information of intelligence value) and suspect engagement. Results revealed that the four MI-consistent behaviours increased information gain. Also, approaches antithetical to MI (including assumptive questioning, judgemental summaries, fighting resistance and accusatory challenges) had a significant negative impact on suspect engagement and, by extension, reduced yield – potentially by creating suspect reactance (where the individual is motivated to regain a freedom they feel is being threatened). Hence, MI approaches are efficacious for information-gathering efforts, and using an approach antithetical to the spirit of motivational interviewing (like pressuring, confronting and judging) with CSA suspects will always make things worse.